2017
DOI: 10.1111/ijn.12553
|View full text |Cite
|
Sign up to set email alerts
|

Support surfaces in the prevention of pressure ulcers in surgical patients: An integrative review

Abstract: There are gaps in knowledge regarding the most efficient support surfaces and the specifications of the products used to prevent pressure ulcers due to surgical positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
18

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
0
22
0
18
Order By: Relevance
“…In order for interventions to be effective in preventing skin injuries, they must be related to pressure relief while and immediately after the patient remains on the operating table, and examples of effective devices for such prevention are dry viscoelastic polymer mattress toppers and gel pads (5) .…”
Section: Introductionmentioning
confidence: 99%
“…In order for interventions to be effective in preventing skin injuries, they must be related to pressure relief while and immediately after the patient remains on the operating table, and examples of effective devices for such prevention are dry viscoelastic polymer mattress toppers and gel pads (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Outro fator de risco no intraoperatório é o tipo de anestesia, que influencia no grau de depressão do sistema nervoso, em que ocorre vasodilatação periférica, resultando em hipotensão e diminuição do retorno venoso, depressão dos receptores da dor, fazendo com que os mecanismos de defesa do paciente não ofereçam mais proteção contra pressão, deixando-os suscetíveis a lesões perioperatórias decorrentes do posicionamento [17][18][19][20] .…”
Section: Discussionunclassified
“…Têm como objetivo evitar atritos, prevenindo LP, compressão ou estiramentos neuromusculares, contato com o metal da mesa, que pode ocasionar queimaduras (devido ao uso do bisturi elétrico) e outros danos 21,22 . Todavia, as superfícies de suporte são pouco utilizadas nos pacientes cirúrgicos, uma vez que as questões políticas, econômicas e sociais enfrentadas pela saúde no país não permitem que muitos serviços públicos disponham desses tipos de recursos tecnológicos, interferindo diretamente na prevenção de lesões [9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Other well-known position-related injuries related to surgery are pressure ulcers, which occur due to unrelieved pressure, usually over bony prominences. The pressure can cause ischaemia, cell death and tissue necrosis (Shaw, Chang, Lee, Kung, & Tung, 2014), and there is evidence of a high incidence of pressure ulcers related to surgical procedures (de Oliveira et al, 2017). The incidence varies greatly, and a previous systematic review found that the incidence ranged from 0.3%-57.4% worldwide (Chen, Chen, & Wu, 2012).…”
Section: Pressure Ulcersmentioning
confidence: 99%